2021
DOI: 10.1038/s41467-021-24430-z
|View full text |Cite
|
Sign up to set email alerts
|

A generative network model of neurodevelopmental diversity in structural brain organization

Abstract: The formation of large-scale brain networks, and their continual refinement, represent crucial developmental processes that can drive individual differences in cognition and which are associated with multiple neurodevelopmental conditions. But how does this organization arise, and what mechanisms drive diversity in organization? We use generative network modeling to provide a computational framework for understanding neurodevelopmental diversity. Within this framework macroscopic brain organization, complete w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
140
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(170 citation statements)
references
References 102 publications
(150 reference statements)
13
140
0
Order By: Relevance
“…This explanation would suggest that probabilistic network wiring becomes less determined in any condition that decreases specificity between neurons. Interestingly, previous GNM work at the whole-brain scale has shown that lower magnitude wiring parameters are associated with poorer cognitive scores 46 , age 46,47 and a diagnosis of Schizophrenia 45,48 . This may suggest convergent evidence for how developmental randomness, intrinsic to how developing parts interact with each other, may influence functional outcomes 100 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This explanation would suggest that probabilistic network wiring becomes less determined in any condition that decreases specificity between neurons. Interestingly, previous GNM work at the whole-brain scale has shown that lower magnitude wiring parameters are associated with poorer cognitive scores 46 , age 46,47 and a diagnosis of Schizophrenia 45,48 . This may suggest convergent evidence for how developmental randomness, intrinsic to how developing parts interact with each other, may influence functional outcomes 100 .…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies employing generative models of human macroscopic structural brain organization have shown that generative rules based on homophilic attachment mechanisms can achieve very good model fits [45][46][47]49 (although see 50 ). But what do homophily-based wiring rules essentially entail?…”
Section: Homophilic Wiring Principles Underpin Developing Rodent Neur...mentioning
confidence: 99%
See 1 more Smart Citation
“…For network neuroscience, null models broadly fall into two categories. Generative null models describe the placement or formation of edges between nodes, often based on simple rules that after repeated application, can form complex topology ( Akarca et al, 2021 ; Vertes et al, 2012 ). Rewiring null models alter the given topology of a network by swapping or reweighting edges, according to specified constraints or rules ( Kaiser & Hilgetag, 2006 ; Roberts et al, 2016 ).…”
Section: Edge-centric Network Analysesmentioning
confidence: 99%
“…A natural extension of sgFC is in the domain of spatially embedded null models that generate surrogate structural or functional networks to benchmark the presence of specific network attributes (Esfahlani, Bertolero, Bassett, & Betzel, 2020;Roberts et al, 2016). Moreover, sgFC may also serve as a quality function for generative models of connectivity Journal: NETWORK NEUROSCIENCE / Title: Benchmarking functional connectivity by the structure and geometry of the human brain Authors: Zhen-Qi Liu, Richard F. Betzel, Bratislav Misic (Akarca, Vértes, Bullmore, & Astle, 2021;Betzel et al, 2016;Oldham et al, 2021;Shinn et al, 2021;Vértes et al, 2012). Finally, we envision sgFC as the basis for more sophisticated network communication models that consider spatial proximity as a constraint for routing signals (Seguin, Razi, & Zalesky, 2019;Seguin, van den Heuvel, & Zalesky, 2018;Vázquez-Rodríguez, Liu, Hagmann, & Misic, 2020b).…”
Section: Discussionmentioning
confidence: 99%